The preoperative platelet–lymphocyte ratio versus neutrophil–lymphocyte ratio: which is better as a prognostic factor in oral squamous cell carcinoma? - Chen, Shan (Ther Adv Med Oncol, 2016)
OBJECTIVE: Recent studies have shown that the presence of systemic inflammation and platelet status correlate with poor survival in various cancers. The aim of this study was to evaluate the prognostic value of the preoperative platelet–lymphocyte ratio (PLR) and the neutrophil–lymphocyte ratio (NLR) in patients with oral squamous cell carcinoma (OSCC) undergoing surgery. METHODS: In this study, 306 patients with OSCC who had surgery were enrolled. The optimal cutoff value of PLR and NLR was determined by receiver operating characteristic (ROC) curve analysis. The prognostic significance of both markers was determined by uni- and multivariate analysis. RESULTS: The results showed that high NLR and PLR were classified using a cutoff value of 2.7 and 135, respectively, based on ROC curve analysis. Only PLR was associated with decreased disease-free survival [hazard ratio (HR) = 2.237; 95% confidence interval (CI): 1.401–3.571; p = 0.001] and overall survival [HR = 2.022; 95% CI: 1.266–3.228; p = 0.003] by both uni- and multivariate analysis. CONCLUSION: The preoperative PLR is superior to NLR as an independent indicator in predicting disease-free survival and overall survival in patients who undergo oral cancer resection for OSCC.